A novel single-phase AC–DC bridgeless boost converter for PFC application. Issue 1 (2nd January 2018) - Lin, Xiang; Wang, Faqiang
ABSTRACT: A novel single-phase AC–DC bridgeless boost power factor correction (PFC) converter is proposed in this paper. This converter is constructed by paralleling a boost and a buck–boost topology. It features a solid connection between the input and output ground terminals leading to low common mode noise. Moreover, it possesses a high PFC performance which can satisfy IEC-61000-3-2 Class D Limits completely and only two semiconductors conducting in the current-flowing path. In addition, the two power switches are driven by the same control signal resulting in a simple controller. The detailed circuit operation principle in discontinuous conduction mode is presented. A simulated model established by PSIM software and a lab prototype is designed to validate the effectiveness of this proposed PFC converter.